Pollution and Resource Extraction: Do they Matter for the Dynamics of Growth? - George Economides; Apostolis Philippopoulos (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper shows that whether pollution occurs as a by-product of economic activity (which is supposed to be the case in DCs), or as resource extraction (which is supposed to be the case in LDCs), matters for the dynamics of the optimal growth-environment-policy link. The context is a dynamic general equilibrium model of endogenous growth, in which private agents treat natural resources as a public good and the government chooses second-best environmental policy. We show that resource extraction can lead to indeterminacy, i.e. many different equilibrium transition paths. This can partly explain the observed persistent differences in growth among LDCs with similar fundamentals and endowments.
Keywords: 330; Pollution and resource extraction; growth; dynamics; second-best policy